Magnetic soft centirobot to mitigate biological threats - Jayraj V. Vaghasiya; Carmen C. Mayorga‐Martinez; Jaroslav Zelenka; Shelja Sharma; Tomas Ruml; Martin Pumera (SmartMat)
Abstract Soft robots have drawn a lot of interest in the field of human–robot interfaces because they can mimic the propulsion of soft bodies and archive complex tasks that cannot be made by rigid robots such as performing the complex motion, avoiding collisions by absorbing impacts, and shape adaptation by elastic deformation. Herein, drawing inspiration from creatures in the Cambrian period, such as Hallucigenia, we develop a centimeter‐sized soft robot with multiple magnetic legs (referred to as a soft centirobot). This robot is equipped with graphitic carbon nitride (g‐C3N4) nanosheets to kill biological threats by photogenerated reactive oxygen species under black light illumination. The motion of g‐C3N4 soft centirobot is controlled by magnetic actuation even in complex wastewater samples (with a relative speed of 0.12 body lengths per second). The magnetic multilegs work as a propeller to walk across and cover large regions, and water disinfection is more efficient than what could be achieved by nano/micrometer scale sheets of g‐C3N4. Finally, factors affecting the accelerated propulsion of g‐C3N4 soft centirobot such as design principle, structure geometry, body mass, driving mechanism, and magnetic sensitivity, have been investigated. We envision that such a photoactive 2D material‐based integrated centimeter‐sized robot shall find application in many areas where pathogen removal is required.